2017
DOI: 10.1002/2017jb014460
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of Induced Slip on the Causative Fault of the 2015Mw4.0 Venus Earthquake, Northeast Johnson County, Texas

Abstract: On 7 May 2015, a Mw 4.0 earthquake occurred near Venus, northeast Johnson County, Texas, in an area of the Bend Arch‐Fort Worth Basin that reports long‐term, high‐volume wastewater disposal and that has hosted felt earthquakes since 2009. In the weeks following the Mw 4.0 earthquake, we deployed a local seismic network and purchased nearby active‐source seismic reflection data to capture additional events, characterize the causative fault, and explore potential links between ongoing industry activity and seism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 61 publications
(130 reference statements)
2
25
0
Order By: Relevance
“…A similar lack of fault offset in sedimentary cover was observed near an induced earthquake swarm in northeastern Texas Scales et al, 2017). The correspondence between earthquake sequences and magnetic gradient peaks or offsets between other linear features in the magnetic anomaly maps suggests that most of the induced earthquakes in Oklahoma involve the reactivation of ancient basement faults.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…A similar lack of fault offset in sedimentary cover was observed near an induced earthquake swarm in northeastern Texas Scales et al, 2017). The correspondence between earthquake sequences and magnetic gradient peaks or offsets between other linear features in the magnetic anomaly maps suggests that most of the induced earthquakes in Oklahoma involve the reactivation of ancient basement faults.…”
Section: Discussionsupporting
confidence: 55%
“…Light gray lines show county boundaries; inset shows location of map relative to Oklahoma. For example, in northeastern Texas Magnani et al (2017) and Scales et al (2017) observed only very limited deformation in sedimentary cover associated with a fault that recently experienced induced earthquakes. The basement faults are better aligned with earthquakes than those in the sedimentary cover.…”
Section: 1029/2018gl077768mentioning
confidence: 99%
“…The model consists of a more permeable (5 × 10 À14 m 2 ) Ellenburger formation, where injection occurs, situated between two comparatively less permeable formations-the Barnett shale (1 × 10 À18 m 2 ) above and granitic basement below (1 × 10 À19 m 2 ) (Hornbach et al, 2015;Loucks et al, 2009). The fault width is approximated to 10 m based on the approximate displacement in the regional faults that is in tens of meters Scales et al, 2017). The fault width is approximated to 10 m based on the approximate displacement in the regional faults that is in tens of meters Scales et al, 2017).…”
Section: Pore Pressure Diffusion Model Methodologymentioning
confidence: 99%
“…Janská and Eisner (2012)used these data to document a cluster of earthquakes about 4 km north of the S-well beginning in May 2010 through January 2012 (hypocenters approximated by green asterisks, Figure 1). Deployment of local seismic stations in the area by SMU, including redeployment of AFDAD in 2014, revealed small-magnitude earthquakes continued at the airport; earthquakes from 2013 to present are reported in the SMU local earthquake catalog (blue asterisks, Figure 1) (Hornbach et al, 2015;Magnani et al, 2017;Scales et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The overall stress state in the Barnett Shale is consistent with normal faulting regime (Snee & Zoback, 2016) where high-dip-angle faults are oriented along the northeast (Figure 1). The optimal receiver fault geometry used for calculating CFS change is summarized in Table S1 Scales et al, 2017;Snee & Zoback, 2016). The focal mechanism of the DFW Airport sequence is not determined but is perceived to be similar to that of the Cleburne and Azle sequences (Frohlich et al, 2011).…”
Section: Hydrogeological Background and Model Setupmentioning
confidence: 99%